Reading and writing in the early grades of elementary school: Challenges and learning in two schools in the municipality of Belém, Pará State (PA), Brazil (Research, Society and Development, 2024)
When we start learning to read and write, we depend on a complex integration of linguistic, neuropsychological and intellectual factors, as well as affective and socio-environmental factors. In the early years of school life, reading and writing are essential tools for a child's all-round development. From the authors' perspective, there is a need not only for activities related to literacy, but also for different themes and practices to be discussed and contextualized in school spaces. We report here on the experience of educational practices carried out in the project "Reading and Writing in the early grades of elementary school" in two public schools in Belém-Pará. Pedagogical practices were developed in which students performed various readings and sequenced words through games, games and playful dynamics. Topics related to reading and writing were discussed in the classroom, providing students with practical learning in a fun and meaningful way to improve their knowledge of these topics. The activities developed are essential for the development of literacy and promote new teaching practices that enhance learning.